Synthesis Method Comparison of N-Doped Carbons for Electrochemical Energy Storage - Palmbahs, Roberts; Lesnicenoks, Peteris; Knoks, Ainars; Vitola, Virginija; Kleperis, Janis (MDPI, 2024)
This study investigates nitrogen-doped carbon synthesis and electrochemical properties as electrode material for energy storage devices, an additional focus of the work is on the electrochemical exfoliation synthesis of nitrogen-doped carbon using various precursors and doping methods. The physical properties of the synthesized sample are characterized using X-ray photoelectron spectroscopy, scanning electron microscopy, and Raman spectroscopy. The electrochemical properties of the N-doped carbons are studied using cyclic voltammetry and galvanostatic charge-discharge cycling. Finally, the work explores the potential application of the N-doped carbons as electrode material for energy storage devices, such as supercapacitors. The results show that N-doped carbons exhibit electrochemical performance superior to that of graphene oxide, with higher electrical capacitance. The results demonstrate the potential of N-doped carbons as high-performance electrode materials for electrochemical energy storage applications. This paper aims to explain the advantages of N-doping in carbon materials more precisely in graphene and the use of these materials in creating electrodes for application in supercapacitors and batteries. © 2024 by the authors. --//-- This is an open-access article Palmbahs, R.; Lesnicenoks, P.; Knoks, A.; Vitola, V.; Kleperis, J. Synthesis Method Comparison of N-Doped Carbons for Electrochemical Energy Storage. ChemEngineering 2024, 8, 80, https://doi.org/10.3390/chemengineering8040080 published under the CC BY 4.0 licence.
Thanks are provided for the financial support from the Latvian Science Council project LZP FLPP No. LZP-2018/1-0194 and Virginija Vitola acknowledge the project LZP-2023/1-0521. Authors acknowledges the Institute of Solid State Physics of the University of Latvia, which as a center of excellence has received funding from the European Union framework program Horizon 2020 H2020-WIDESPREAD-01-2026-2017-TeamingPhase2 within the framework of grant agreement No. 739508 of the CAMART2 project.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; carbon materials; electrochemical exfoliation; graphene; supercapacitors